2019
DOI: 10.35741/issn.0258-2724.54.4.35
|View full text |Cite
|
Sign up to set email alerts
|

Inclined Magnetic Field of Non-uniform and Porous Medium Channel on Couple Stress Peristaltic Flow and application in medical treatment (Knee Arthritis)

Abstract: The present study analyzes the effect of couple stress fluid (CSF) with the activity of connected inclined magnetic field (IMF) of a non-uniform channel (NUC) through a porous medium (PM), taking into account the sliding speed effect on channel walls and the effect of nonlinear particle size, applying long wavelength and low Reynolds count estimates. The mathematical expressions of axial velocity, stream function, mechanical effect and increase in pressure have been analytically determined. The effect of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…( 16) into Eqs. (12 -15), giving us the equations: 2 ) + 𝑅 𝑑 (πœƒ 4 ) 𝑦𝑦 + 𝛽 (20) π‘Šβ„Žπ‘’π‘Ÿπ‘’ 𝑃 π‘š is the sum magnetic and ordinary pressure, which is the total pressure. The corresponding stream function, temperature function, and magnetic force function boundaries for non-conductive elastic walls in the wave frame are as follows:…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…( 16) into Eqs. (12 -15), giving us the equations: 2 ) + 𝑅 𝑑 (πœƒ 4 ) 𝑦𝑦 + 𝛽 (20) π‘Šβ„Žπ‘’π‘Ÿπ‘’ 𝑃 π‘š is the sum magnetic and ordinary pressure, which is the total pressure. The corresponding stream function, temperature function, and magnetic force function boundaries for non-conductive elastic walls in the wave frame are as follows:…”
Section: Problem Formulationmentioning
confidence: 99%
“…This mechanism is well known to physiologists as one of the principle mechanisms for fluid transportation. Peristaltic mechanisms are utilized in a variety of industrial applications and biomedical, this mechanism is helpful in many different systems, including the motion of ovulation in the fallopian channel, the swallowing of food down to the stomach, the flow of tiny blood vessels, blood pump in the heart-lung machine, and the transport of urine from the renal to the bladder [4]. There are some academic research has investigated the peristaltic flow process of nanofluids, and some of these researches, including .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the inclined magnetic field on the peristaltic transport of a non-Newtonian fluid in an antisymmetric porous channel is discussed. The non-Newtonian fluid is a hyperbolic tangent fluid model [12]. Hatem studied the analysis of the effect of rotation on the analysis of heat transfer by mixed convection for the peristaltic transport of a viscous liquid in an asymmetric channel [13].…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that when there is an increased power law index, then there will be also an increase of the temperature and velocity of Hyperbolic tangent fluid, the concentration is decreased as n increases, and the size of trapped bolus is increased. Hummady and Ridha [10] lately provided their research work on the impacts of magnetic field on peristaltic flows in anti-symmetric channel with porous media, and showed their results where the flow induced via peristaltic transport of the channel wall is analysed under same assumptions of Reynolds number and wave-length, and velocity and stream function are determined. The trapping phenomenon is thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%